White-spot disease of Chinese soft-shelled turtles (Trionyx sinens) caused by Paecilomyces lilacinus - Li, Xiao-liang (Zhejiang University Press, 2008)

(untitled)
Chinese soft-shelled turtles (Trionyx sinens) in culture farms using an artificial warming system in Zhejiang, China, often show typical signs of white-spot disease such as white spots on their bodies, skin lesions, anorexia and eventually death. The sick turtles were mostly 5~80 g in weight. A suspected fungal pathogen was isolated from the sick turtles and verified as Paecilomyces lilacinus by sequence analysis of the internal transcribed spacer (ITS) of its ribosomal DNA (rDNA). Detailed morphological examinations were also conducted to confirm the white-spot disease.